2017
DOI: 10.1007/s13340-017-0318-y
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of short-term toe resistance training in patients with type 2 diabetes mellitus

Abstract: Objective The purpose of this pilot study was to investigate the effect of short-term toe resistance training on toe pinch force and toe muscle quality in patients with type 2 diabetes mellitus. Methods A total of 12 patients with type 2 diabetes mellitus who were hospitalized to improve glycemic control (8 men and 4 women, duration of diabetes 12.2 ± 9.5 years) were enrolled in this pilot study. Exercise therapy was performed with conventional aerobic exercise and four newly developed toe resistance training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…This means that the formation of alternative pathways for CST recovery is likely to be accelerated in an activity-dependent manner in the brain. A recent clinical study showed that only 2 weeks of toe resistance training improved pinch force and knee extension force in humans with DN [ 212 , 213 ]. Gains in strength during such short-term training have been attributed to adaptations within the CNS [ 214 , 215 ].…”
Section: Alteration Of Corticomotoneuronal Pathwaymentioning
confidence: 99%
“…This means that the formation of alternative pathways for CST recovery is likely to be accelerated in an activity-dependent manner in the brain. A recent clinical study showed that only 2 weeks of toe resistance training improved pinch force and knee extension force in humans with DN [ 212 , 213 ]. Gains in strength during such short-term training have been attributed to adaptations within the CNS [ 214 , 215 ].…”
Section: Alteration Of Corticomotoneuronal Pathwaymentioning
confidence: 99%
“…Nine of the selected studies were published during 2012–2016 ( 28 , 32–34 , 39–41 , 51 , 54 ). However, there has been a rapid increase in research studies over recent years, with 19 further studies published during 2016–2022 ( 29–31 , 35–38 , 42–50 , 52 , 53 , 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…A randomized control trial (RCT) research design comprised 54% of the studies ( 28–33 , 35 , 36 , 39–42 , 44 , 51 , 52 ); pilot study research designs were used in another 14% ( 34 , 43 , 48 , 50 , 55 ); the other designs were interviews (10%) ( 38 , 47 , 49 ); experimental designs (10%) ( 37 , 46 , 53 ); a crossover control study (4%) ( 54 ); a cohort study (4%) ( 45 ); and a feasibility study (4%) ( 48 ). In total, 10 types of exercise interventions were used: these included aerobic exercise ( 28 , 32–35 , 37–42 , 44–47 , 49 , 50 , 52–54 ); resistance exercise ( 31 , 33–35 , 37–42 , 44–51 , 55 ); balance exercise ( 38 , 39 ); core exercise ( 39 ); computer-based exercise intervention ( 43 ); sling exercise therapy ( 29 ); video-guided exercise ( 30 ); flexibility exercise ( 38 ); respiratory exercise ( 35 ); and progressive relaxation exercises ( 36 ). The studies all included positive results, except for one.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations